Paspalum vaginatum Extract-Mediated Synthesis of ZnO Nanoparticles and Assessment of their Photocatalytic and Antibacterial Activities - Anuforo, Henry U.; Abara, Priscilla N.; Chiegboka, Nneamaka A.; Udebuani, Angela C.; Ibeh, Olusola O.; Nnokwe, Justin C.; Adjeroh, Lawrencia A.; Ogbulie, Toochukwu E. (Asian Journal of Chemistry, 2025)
Phytochemical screening of Paspalum vaginatum extract was conducted prior to its use in the biosynthesis of zinc oxide nanoparticles (ZnO NPs), which were subsequently characterized using several analytical techniques. Results revealed high concentrations of carbohydrates, alkaloids, amino acids and proteins, phenolic compounds and flavonoids in the extract. UV-visible spectrum of biosynthesized ZnO NPs showed maximum absorbance at 307 nm. The X-ray diffraction (XRD) pattern confirmed a hexagonal wurtzite crystalline structure, with an estimated crystallite size of 23.6 nm. Resulting transmission electron micrograph (TEM) revealed spherical-shaped ZnO NPs, with average size of 3.96 ± 2.4 nm. Antibacterial analysis against isolates of Salmonella typhi and Staphylococcus aureus produced 11.33 ± 7.2 mm and 16 ± 3.2 mm zones of inhibition at 53.3 µg/mL, respectively. Also, percentage degradation of methyl orange dye solution was 13.16 ± 1.8%, 28.84 ± 0.6% and 32.74 ± 3.1% using 1.72 mg/mL of ZnO NPs, after 1, 2 and 3 h of solar irradiation. Thus, P. vaginatum extract is suitable for biogenic synthesis of ZnO NPs which possess appreciable bioactivities.